1995
DOI: 10.1101/gad.9.1.72
|View full text |Cite
|
Sign up to set email alerts
|

CPSF recognition of an HIV-1 mRNA 3'-processing enhancer: multiple sequence contacts involved in poly(A) site definition.

Abstract: The endonucleolytic cleavage and polyadenylation of a pre-mRNA in mammalian cells requires two c/s-acting elements, a highly conserved AAUAAA hexamer and an amorphous U-or GU-rich downstream element, that together constitute the "core" poly(A) site. The terminal redundancy of the HIV-1 pre-mRNA requires that the processing machinery disregard a core poly(A) site at the 5' end of the transcript, and efficiently utilize an identical signal that resides near the 3' end. Efficient processing at the 3' core poly(A)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
141
0

Year Published

1995
1995
2013
2013

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 119 publications
(149 citation statements)
references
References 52 publications
8
141
0
Order By: Relevance
“…In addition to the AAUAAA motif and the downstream GU-rich or U-rich element of mammalian systems, upstream sequences that contribute to the efficiency of mRNA 3Ј end formation were also identified in the mammalian viruses simian virus 40 (6,36), adenovirus (8,9), hepatitis B virus (29), and human immunodeficiency virus type 1 (3,11,12,38,39). These elements function in an orientation-and position-dependent manner, and several appear to be functionally analogous.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the AAUAAA motif and the downstream GU-rich or U-rich element of mammalian systems, upstream sequences that contribute to the efficiency of mRNA 3Ј end formation were also identified in the mammalian viruses simian virus 40 (6,36), adenovirus (8,9), hepatitis B virus (29), and human immunodeficiency virus type 1 (3,11,12,38,39). These elements function in an orientation-and position-dependent manner, and several appear to be functionally analogous.…”
Section: Discussionmentioning
confidence: 99%
“…The nucleotide sequence surrounding the cleavage site is not strictly conserved [51,52]. In vertebrate pre-mRNAs, 70% of the cleavage sites are located at the 3′ side of an adenosine residue [53], with a nucleotide preference of A > U > C ≫ G. The nucleotide preceding the cleavage site is cytosine in 59% of 269 pre-mRNA sequences examined [53], making the optimal cleavage site CA (Fig.…”
Section: The Downstream Element (Dse)-mentioning
confidence: 99%
“…The regulated use of poly(A) signals in retroviruses such as HIV-1 has been the subject of extensive scientific research over the past decade+ The duplication of this poly(A) signal in both 59 and 39 long terminal repeats (LTR) of the provirus necessitates the evolution of a mechanism to selectively activate the poly(A) signal in the 39 LTR but suppress its use in the 59 LTR (Proudfoot, 1991)+ Figure 1A summarizes the arrangement of these two poly(A) signals within the overall structure of the provirus+ A number of different mechanisms have been indicated to achieve this tight regulation+ First, in the 39 LTR, the poly(A) signal may be significantly enhanced by upstream sequence elements+ In the case of HIV-1, it has been shown that sequences in the U3 region activate the adjacent poly(A) signal as shown by experiments using the whole provirus (Ashe et al+, 1995) as well as in vitro RNA processing studies (Gilmartin et al+, 1992)+ These latter experiments further show that U3-enhancing sequences aid the recruitment of the principal cleavage/polyadenylation factor CPSF, which specifically interacts with the AAUAAA sequence motif (Gilmartin et al+, 1995)+ In the 59 LTR the inactivity of the HIV poly(A) site cannot be fully accounted for by the absence of U3 enhancing sequences, because the minimal HIV-1 poly(A) signal is still a relatively strong RNA processing signal (Weichs an der Glon et al+, 1991)+ Several mechanisms have therefore been proposed that may act to block the activity of this poly(A) signal+ The close proximity of the poly(A) signal to the proviral transcription start site has been implicated in the suppression process (Weichs an der Glon et al+, 1991Glon et al+, , 1993Cherrington & Ganon, 1992)+ Whether this suppression is achieved by the proximity of the transcription initiation complex or the nearby presence of the Cap structure in the pre-mRNA was not determined+…”
Section: Introductionmentioning
confidence: 99%